2020
DOI: 10.1016/j.ajhg.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Clustering of Missense Variants in HNF1A Using Multidimensional Functional Data Aids Clinical Interpretation

Abstract: Summary Exome sequencing in diabetes presents a diagnostic challenge because depending on frequency, functional impact, and genomic and environmental contexts, HNF1A variants can cause maturity-onset diabetes of the young (MODY), increase type 2 diabetes risk, or be benign. A correct diagnosis matters as it informs on treatment, progression, and family risk. We describe a multi-dimensional functional dataset of 73 HNF1A missense variants identified in ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Recently, an evaluation of different HNF1A mutations and their effects on clinical parameters were made. The results showed that the best and superior readout that correlated to clinical phenotype was for the transcriptional activity of the gene, therefore it was suggested that new high-throughput functional screens should be developed [ 53 ]. Interestingly, a homozygous missense HNF1A (pA251T) variant related to MODY was described recently [ 32 ].…”
Section: Molecular Pathophysiology Of the Most Common Mody Subtypesmentioning
confidence: 99%
“…Recently, an evaluation of different HNF1A mutations and their effects on clinical parameters were made. The results showed that the best and superior readout that correlated to clinical phenotype was for the transcriptional activity of the gene, therefore it was suggested that new high-throughput functional screens should be developed [ 53 ]. Interestingly, a homozygous missense HNF1A (pA251T) variant related to MODY was described recently [ 32 ].…”
Section: Molecular Pathophysiology Of the Most Common Mody Subtypesmentioning
confidence: 99%
“…More recently, our appreciation for the role of HNF1A in MODY has been expanded, as homozygous hypomorphic variants have also been identified as a cause of MODY (Misra et al 2020). These observations fit with a growing body of evidence demonstrating that genetic variation across the functional severity spectrum corresponds to phenotype (Althari et al 2020).…”
Section: Hepatocyte Nuclear Factor 1 Alpha (Hnf1a-mody Mody3)mentioning
confidence: 54%
“…Functional studies have demonstrated that proteintruncating mutations result in haploinsufficiency (Harries et al 2004), whilst missense variants lead to loss of function through a variety of mechanisms (Althari et al 2020). More recently, our appreciation for the role of HNF1A in MODY has been expanded, as homozygous hypomorphic variants have also been identified as a cause of MODY (Misra et al 2020).…”
Section: Hepatocyte Nuclear Factor 1 Alpha (Hnf1a-mody Mody3)mentioning
confidence: 99%
See 1 more Smart Citation
“…While some of them are associated with MODY3, e.g. the P291fsinsC mutation in exon 4 that is the most common Colclough, 2006, Colclough et al, 2013), others confer susceptibility for developing T2D, or are benign and neutral (Althari et al, 2020). MODY3 has high penetrance and is a very variable disease, even in siblings presenting severe insulin secretion defects.…”
Section: Hnf1a Mutations (Mody3)mentioning
confidence: 99%